A new preparation of colloidal 99mTc-Tin phosphate stabilized with CMC as lyophilized kit for bone Marrow Scintigraphy - Alaa K. Jabbar; Husham M. Abdul-Kareem (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2010)
The new preparation of colloidal Tin phosphate labeled with technisum- 99m for bone marrow studies. The method was applied with heating sodium bi hydrogen phosphate with carboxy methyl cellulose (CMC) as stabilizer in neutral medium then cooed at room temperature, followed by adding stannous chloride as stannite. The chemical analysis indicates that the radiochemical purity is greater than 99% with suitable particle size distribution. The results of biodistribution indicate that the preparative agent was accumulated with higher concentration in bone marrow reach to 30% of total injected dose and negligible percent in non target organs. The results meaning that the new preparative agent is a good agent for using as bone marrow scintigraphy compared with others.